MINERALS DEFICIENCY IN IRAQI PATIENTS UNDERWENT TO SLEEVE GASTRECTOMY SURGERY - Aymen Radhi Habeeb; Dina A. A. Abdullah; Hamid AL-Tameemi (European Science Publishing, 2025)
Background: Sleeve gastrectomy (SG) is simple, relatively safe, and more effective procedure which gained more popularity to reduce the weight in morbidly obese patients and reduce the obesity complications. However, some consequences still unknown. Therefore, the Aim of the study designed to evaluate the outcomes of nutrients elements deficiency in Iraqi patients underwent to sleeve gastrectomy.
Keywords: Minerals Deficiency; Sleeve gastrectomy surgery, SG, Vitamin, supplements.